Smoking effect on the interleukin-1β expression and periodontal status of periodontitis patients - Muhammad Ihsan Rizal; Redha Putri Wiranda; Ria Aryani Hayuningtyas; Fatimah Maria Tadjoedin; Ferry Sandra; Melanie Sadono Djamil (Wolters Kluwer Medknow Publications, 2022)
Background: The smoking habit is a risk factor for periodontitis. Periodontitis is a multifactorial inflammatory disease associated with biofilm plaque dysbiosis and is characterized by the progressive deterioration of the periodontal tissue. Pro-inflammatory cytokines, such as interleukin-1β (IL-1β), can trigger inflammation of the tissue and become a stimulator to destroy it. Moreover, IL-1β will increase in response to inflammation. Objective: The aim of this study was to evaluate the differences in periodontal status and IL-1β gene expression between smoking and nonsmoking periodontitis subjects. Methods: This research was an analytic observational study with a cross-sectional design. The anthropometric demographic data included name, address, gender, age, plaque index examination, papillary bleeding index (PBI), calculus index, smoking status, and clinical photos to diagnose periodontitis. The collection of gingival crevicular fluid and the analysis of the IL-1β gene expression were conducted using real-time polymerase chain reaction. Results: There were significant differences in periodontal status for plaque index, calculus index, debris index, oral hygiene index, and PBI between smoking and nonsmoking subjects. The IL-1β gene expression was significantly higher (P = 0.047) in smoking subjects than in nonsmoking subjects, with mean ± standard deviation (11.34 ± 9.11) and (0.24 ± 0.42), respectively. Conclusion: This study revealed differences in periodontal status and the IL-1β gene expression between smok ing and nonsmoking periodontitis subjects. The periodontal rate was higher in periodontitis smokers compared to nonsmokers periodontitis. In this study, it was also found that the expression of the IL-1β gene was significantly higher in subjects with smoking periodontitis.